Synthesis of magnetic carbon nanocomposites by hydrothermal carbonization and pyrolysis - Siddiqui, M.; Nizamuddin, S.; Baloch, H.; Mujawar, Mubarak; Dumbre, D.; Inamuddin; Asiri, A.; Bhutto, A.; Srinivasan, M.; Griffin, G. (Springer, 2018)
The fabrication of magnetic carbon nanostructures is emerging to develop composites with unique properties. Consolidating magnetic nanoparticles with carbon materials can be used in nanoelectronics, catalysis, optical application, biosensors, environmental remediation, energy, hydrogen storage, drug transport, magnetic resonance imaging and cancer diagnosis. In addition, thermochemical methods such as hydrothermal carbonization and pyrolysis are low energy processes that offer an efficient synthesis of the controlled morphology of magnetic carbon nanocomposite. These methods provide chemical and morphological improvements of the structure, such as high surface area, ordered nanosizes, crystal matrix, material stability, electrical conductivity, magnetic s aturation and coercivity. This paper reviews the fabrication and properties of magnetic carbon nanocomposites.